THE YOUTH AS A SOCIAL GROUP IN TERMS OF THE SCIENTIFIC EFINITIONS - Sylwester, GŁÓD; MIOTŁA, Piotr (Trends in education, 2014)
It attempted to show in publication scientific definitions of youth in four basic areas: generational, which draws attention to the existence fact of the intergenerational changes among the youth; individual, which treats the youth as the collection of individuals; cultural anthropological where the environment in which young people grow up is a factor conditioning their attitudes and definitions which adopted biological frames or age as the determinant .
Keywords: didactics; youth; research; scientific definition.